2001
DOI: 10.1097/00004836-200105000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Familial Cluster of Fulminant Hepatitis A Infection

Abstract: Hepatitis A virus is a common cause of a self-limited liver disease. Fulminant hepatitis is a rare complication of acute hepatitis A infection. We report a small epidemic of three consecutive fulminant hepatitis A infections in three previously healthy siblings. This is the first report of a cluster of fulminant hepatitis A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Some studies suggested the relationship between disease severity and viral load, 30,31 some strains or amino acid change in the 2B region. [31][32][33][34] Fourth, histopathological evaluation was performed in only one patient. To understand the underlying mechanisms of AKI, histopathological evaluations should be performed on available patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested the relationship between disease severity and viral load, 30,31 some strains or amino acid change in the 2B region. [31][32][33][34] Fourth, histopathological evaluation was performed in only one patient. To understand the underlying mechanisms of AKI, histopathological evaluations should be performed on available patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that disease severity depends on host factors including age and underlying chronic liver disease [Muraoka, 1990;Vento et al, 1998]. On the other hand, it was reported that young healthy persons were also at risk for severe complications, based on the outbreak of an urban epidemic of hepatitis A in the United States [Willner et al, 1998], in which a cluster of fulminant hepatitis A was reported [Durst et al, 2001]. Analysis of factors contributing to disease severity revealed no significant differences in patients' factors including age [Fujiwara et al, 1995[Fujiwara et al, , 2000], suggesting that viral factors and the individual immune responses might determine the severity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study of 3 familial cases of FH A suggested that some strains of HAV might be particularly pathogenic. 22 HAV strains isolated to date have been divided into 7 genotypes based on the criterion of 15% to 20% nucleotide sequence diversity over a 168-base segment at the VP1/2A junction. In our series, patients infected by genotype IA strains (which predominate in France) had a lower incidence of FH, but the difference was not significant in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%